Big Data Analysis on Smartcampus Applications IAIN Syekh Nurjati Cirebon : A Preliminary Study - Saluky Saluky (Procediamath, 2017)
The growth of data so rapidly that it is necessary to anticipate in accommodating the amount of data so large that in the Big data is divided into 3 V namely high-volume, high-velocity and high-variety information, this study is a preliminary study in big data analysis in universities in This initializes the Smart Campus Application in order to be analyzed in Big data obtained structured data and unstructured data that can be processed into useful information for the institution.